Gas composition studies at the 2015 atlas TRT test beam - Çelebi, Emre. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
Transition Radiation Tracker (TRT) is a subsystem of the ATLAS inner detector. It provides many hits on charged particle tracking and helps particle identi cation by measuring transition radiation. At the end of the rst run of the Large Hadron Collider, TRT has su ered from some unforeseen e ects where caused miniature cracks in its gas pipes. These resulted in gas leaks at a level where using the usual Xenon based gas mixture was no longer feasible in certain parts of the detector. In an e ort to understand the transition radiation photon capture performance of the substitute gas mixtures, Krypton-based and Argon-based mixtures, test beam studies using a smaller transition radiation detector (TRD) were undertaken during 2015. In this thesis, we present; this test detector, the relevant test-beam setup, the calibration of the system, the analysis of the data and the results in the form of probability-to-exceed-threshold plots; which can be used as input to future detailed Monte Carlo simulations that are needed to de ne optimal TRT operating points with substitute gas mixtures. Our results veri ed that the transition radiation performance of the Krypton gas mixture is better than the Argon mixture but is outperformed by the original Xenon mixture.
Keywords: Transition Radiation.; ATLAS Transition Radiation Tracker.